Quantitative analysis of the benzanthrone aminoderivative binding to amyloid fibrils of lysozyme - Vus, K.O.; Trusova, V.M.; Gorbenko, G.P.; Kirilova, E.; Kirilov, G.; Kalnina, I. (Харьковский Национальный Университет им. В.Н.Каразина, 2010)
The accumulation of amyloid fibrils in different tissues is associated with a number of neurodegenerative diseases. Despite a huge variety of amyloid-specific probes, all of them suffer from many drawbacks, highlighting the necessity of searching for more preferable dyes. In the present work, the potential of new fluorescent probe AM3 for selective detection of fibrillar protein aggregates, formed from lysozyme, has been evaluated. To quantify the affinity of this dye for amyloid fibrils, the isotherms of dye binding to the fibrillar lysozyme have been derived from fluorimetric titration. Parameters of the dye-protein complexation: association constant, molar fluorescence and binding stoichiometry, calculated from the Langmuir adsorption model, revealed that AM3 interacts strongly with protein insoluble aggregates. High values of the binding parameters make AM3 an alternative to a widely-used amyloid-specific probe Thioflavin T. We also investigated the effects of polarity and viscosity on AM3 fluorescence properties. The binding of AM3 to the protein hydrophobic cavities has been followed by red shift of the dye emission spectra, which can be explained by H-bonding between proton-donating groups of the protein and carbonyl moiety of the probe. Long-wavelength shift of emission maximum was observed also upon increasing the excitation wavelength. This finding suggests that reorientation time of solvent molecules is higher, than the dye fluorescence lifetime. Fluorescence anisotropy studies revealed slow rotation diffusion of the probe, bound to amyloid fibrils being indicative of high viscosity of AM3 microenvironment. The observed photophysical properties of the new aminobenzanthrone derivative make AM3 a perspective probe for basic research and medical diagnostics.
Keywords: amyloid fibrils; benzanthrone fluorescent dye; dye-protein binding; lysozyme